Association of perioperative intravenous lignocaine and intraoperative neuromonitoring in adolescent idiopathic scoliosis surgery: a retrospective study - Siti Nadzrah Yunus; Huey Nee Chong; Zheng-Yii Lee; Rosmalinda Osman; Khean Jin Goh; Chee Kidd Chiu; Chris Yin Wei Chan; Mun Keong Kwan; Mohd Shahnaz Hasan (Perioperative Medicine)
Abstract Background The use of intravenous (IV) lignocaine as an analgesic adjunct is increasing, but its impact on intraoperative neurophysiological monitoring (IONM) remains unclear. This study aimed to evaluate the association between IV lignocaine and somatosensory evoked potential (SSEP) and motor evoked potential (MEP) during adolescent idiopathic scoliosis (AIS) surgery. Methods This retrospective study involved AIS patients who underwent single-stage posterior spinal fusion at a tertiary university hospital from 2020 to 2023. In addition to total intravenous anaesthesia (TIVA), patients who received IV lignocaine (1.5 mg/kg bolus at induction followed by 2 mg/kg/h infusion until wound closure) were included (lignocaine group) and matched with those who did not (standard group). Two neurophysiologists independently reviewed SSEP and MEP recordings at five-time points: T1 (10 min post-induction), T2 (during pedicle screw insertion), T3 (during rod insertion or deformity correction), T4 (start of wound closure, 30 min before surgery end), and T5 (post-skin closure). Neurophysiological changes were clinically significant if MEP or SSEP showed > 50% amplitude reduction or > 10% latency increase. Results A total of 115 AIS patients receiving TIVA were analysed, 59 in the lignocaine group and 56 in the standard group. Demographics and vital signs were comparable. The mean intraoperative propofol dose was significantly lower in the lignocaine group (766.77 ± 315.86 mg vs 928.55 ± 242.93 mg; p = 0.003). MEP amplitudes over the right tibialis anterior and bilateral abductor hallucis were significantly reduced in the lignocaine group (p < 0.05). SSEP analysis revealed significant amplitude reduction and latency prolongation at the left cortical in the lignocaine group at all time points (p < 0.05). Longitudinal changes (T1–T4) in amplitude and latency for both MEP and SSEP were small and not clinically significant. Conclusion Perioperative IV lignocaine infusion during TIVA for AIS surgery significantly reduced MEP and SSEP amplitudes and prolonged SSEP latency, though lacking clinical significance.